Educational offer in older adult home care for migrant family care assistants: results from a multiple qualitative case study - Santini, Sara; Frontalini, Vanessa; Casanova, Georgia; Cancellieri, Serena; Grignoli, Daniela; Golino, Antonella; Moretti, Veronica; Pronzato, Riccardo; Chirico, Ilaria; Chattat, Rabih (Frontiers in Public Health, 2025)
IntroductionThe increasing number of older people with multiple chronic diseases determines care demand, while the number of formal and informal caregivers is decreasing. In many EU countries, migrant family care assistants (MFCAs) bridge the gap between supply and demand of H24 tailored home care, often without training in older adult care. This study aims to explore older adult care education for (migrant) family care assistants at the European level, highlighting strengths and weaknesses to improve training.Methods26 older adult care courses were identified through desk research carried out between December 2023 and March 2024 and analyzed. Information regarding curricula, contents, length, and teaching methods was extracted and compared to identify common and specific characteristics of the training programs.ResultsFindings highlighted an often expensive, unstandardized, and jeopardized offer of older adult care education and the scarcity of training, addressing the emotional, cultural, social, and linguistic needs of MFCAs because learners are not consulted during the course design.DiscussionCourses should be co-funded by the public administration to ensure access for low-income people, co-designed with the target and embedding host country socio-cultural contents and migration/work legislation. Lessons on dementia, behavioral disorders, cognitive stimulation, and internships at older people’s homes, supervised by the Public Authority, are recommended.